Sicyos angulatus ameliorates acute liver injury by inhibiting oxidative stress via upregulation of anti-oxidant enzymes. (1st January 2018) - Kim, Hyun-Yong; Noh, Jung-Ran; Moon, Sung-Je; Choi, Dong-Hee; Kim, Yong-Hoon; Kim, Kyoung-Shim; Yook, Hong-Sun; An, Jin-Pyo; Oh, Won-Keon; Hwang, Jung Hwan; Lee, Chul-Ho
ABSTRACT: Objective: We aimed to investigate the effect of Sicyos angulatus (SA) ethanolic extracts as antioxidants and potential treatments for liver disease. Methods: To establish a mouse model of liver injury, C57BL/6 male mice were injected via the caudal vein with a single dose of concanavalin A (Con A, 15 mg kg −1 ). SA extracts were administered once by oral gavage 30 min before Con A injection. Results: In vitro studies showed that SA decreased tert -butyl hydroperoxide ( t -BHP)-induced reactive oxygen species (ROS) production. SA administration reduced plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, as well as hepatic ROS levels, in a dose-dependent manner. Moreover, SA increased the activities of the hepatic antioxidant enzymes superoxide dismutase, catalase, and glutathione peroxidase in a dose-dependent manner. Furthermore, SA treatment reduced pro-apoptotic protein levels. Con A-mediated cytosolic release of Smac/DIABLO and apoptosis-inducing factor (AIF), which are markers of necrosis, were dramatically decreased in HepG2 cells treated with SA. Conclusion: SA ameliorated liver injury and might be a good strategy for the treatment of liver injury.